How We Manage Social Relationships Through Answers to Questions: The Case of Interjections. Issue 3 (3rd April 2019) - Stivers, Tanya
ABSTRACT: In this article I examine the range of possible answers to polar questions. The focus is on contrasting varieties of interjection answers with each other and with other answer types. I introduce three new types of interjections and discuss how each type functions relative to one another and relative to other classes of answer to propose what interactional and relational work question recipients accomplish through these answer types. Specifically, I argue that although interjections, as a class, accept the questioner's primary question agenda and design as well as the questioner's agency over the proposition of the question—aspects of the question that other answer classes challenge—marked interjection subclasses contrast with unmarked interjections in proposing that there is a problem with regard to asking the question, answering it, or with the action agenda and agency of the proposition. Each subtype of interjection has different implications for the questioner or question recipient and can be understood as subtly managing who they are to each other.